Audio-visual simultaneity judgments. - Zampini, M; Guest, S; Shore, D; Spence, C (2005)
The relative spatiotemporal correspondence between sensory events affects multisensory integration across a variety of species; integration is maximal when stimuli in different sensory modalities are presented from approximately the same position at about the same time. In the present study, we investigated the influence of spatial and temporal factors on audio-visual simultaneity perception in humans. Participants made unspeeded simultaneous versus successive discrimination responses to pairs of auditory and visual stimuli presented at varying stimulus onset asynchronies from either the same or different spatial positions using either the method of constant stimuli (Experiments 1 and 2) or psychophysical staircases (Experiment 3). The participants in all three experiments were more likely to report the stimuli as being simultaneous when they originated from the same spatial position than when they came from different positions, demonstrating that the apparent perception of multisensory simultaneity is dependent on the relative spatial position from which stimuli are presented.